Comparison of carbon dioxide fluxes over sandy grassland vegetation as measured by the eddy-covariance technique and by open system chamber - Balogh, János (Acta Biologica Szegediensis, 2005)
Within the frame of an EU sponsored study (Greengrass) CO2 flux measurements were started on differently managed grassland ecosystems. We utilized two techniques– eddy-covariance (EC) and open system gas exchange chamber (OC) – to measure CO2 fluxes and compare the results of the two different methods. The study period presented in this paper covers 2003 and 2004, when the weather conditions were substantially different. OC measurements were made during the nine measurement campaigns in the two years. In comparison with EC the open system chamber proved to be a good tool for gas exchange measurements in grasslands.